2004
DOI: 10.1007/bf03018771
|View full text |Cite
|
Sign up to set email alerts
|

Vein pretreatment with magnesium sulfate to prevent pain on injection of propofol is not justified

Abstract: P Pu ur rp po os se e: : Propofol produces anesthesia with rapid recovery. However, it causes pain or discomfort on injection. A number of techniques have been tried for minimizing propofol-induced pain with variable results. We have compared the efficacy of magnesium and lidocaine for the prevention of propofol induced pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
1
22
1
1
Order By: Relevance
“…injection of propofol in the lidocaine group was 8% and it was similar to the results of Pang and colleagues 12 who reported it to be 11%. But, in some other studies higher incidences, such as 18% 13 or 42%, 11 have been reported. In these studies, the vein on the dorsum of the hand and the pneumatic tourniquet technique was used, as in the present study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…injection of propofol in the lidocaine group was 8% and it was similar to the results of Pang and colleagues 12 who reported it to be 11%. But, in some other studies higher incidences, such as 18% 13 or 42%, 11 have been reported. In these studies, the vein on the dorsum of the hand and the pneumatic tourniquet technique was used, as in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…It was different from the previous studies that the incidence of pretreatment pain of lidocaine and control groups was unexpectedly high in our study. 11 In our study, the overall incidence of pain during i.v. injection of propofol in the lidocaine group was 8% and it was similar to the results of Pang and colleagues 12 who reported it to be 11%.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium is not only the physiological calcium channel blocker, but also an antagonizer of NMDA receptors, which may interfere in the ion channels of K + and Ca 2+ , resulting in reduction of pain perception [20] . In previous studies [5,21,22] , pretreatment with magnesium sulfate was effective in the prevention of propofol-induced pain without considering injection pain from magnesium itself. Incidence of propofol injection pain in a study by Honarmand et al was 34% with magnesium sulphate 2.48 mmol pretreatment [21] .…”
Section: Discussionmentioning
confidence: 97%
“…As shown in previous data, the incidence of propofol-induced pain varies between 28% and 90% in adults [1,2] . Efforts to relieve this pain have been attempted like diluting the propofol solution [3] , addition of lidocaine and pretreatment with ondansetron [4] , magnesium sulfate [5] , opioids, parecoxib [6] , nitroglycerin [7] , and dexmedetomidine [8] . However, none have been found to be totally convenient and effective.…”
mentioning
confidence: 99%
“…Furthermore, elevated ionic strength (for example, MgSO 4 or NaCl) is used in models of muscle and visceral "pain" (Fukawa et al, 1980;Gyires and Torma, 1984;Graven-Nielsen and Mense, 2001). Indeed, injections of MgSO 4 in the clinic are reported as being intensely painful (Agarwal et al, 2004), and NaCl produces a very familiar "burning" pain when applied to injured tissue, hence the phrase "rubbing salt into wounds." These disturbances in extracellular ion concentrations are perceived as painful because they activate nociceptive sensory neurons.…”
Section: Introductionmentioning
confidence: 99%